Appraisal Of Educational Strategies Supporting Vulnerable Children During Covid 19 Disruptions In Public Secondary Schools In Kenya: A Case Of Nakuru County - Wambugu, Kihara Daniel (Machakos University Press, 2021)
students suffered tragic loss in various dimensions. With no physical schooling going on, these children missed out on safe learning environment, lacked assurance for regular meals, and endured considerable levels of stress and abuse at home amidst deteriorating economic conditions. Despite government’s commitment to provide seamless transition to virtual learning, most vulnerable learners lacked equitable accesses to learning due to the existing digital divide and low electricity connection in the rural areas. This study aimed at appraising the education strategies for supporting vulnerable children during COVID-19 disruptions in public secondary schools in Kenya, with specific focus on Nakuru County. The study’s objectives were to evaluate the impact of distribution of online resources, addressing socio-emotional needs, and parental engagement on supporting vulnerable students during COVID-19 disruptions in public secondary schools in Nakuru County. The study used descriptive survey design. The target population was 4510 individuals, comprising of 294 principals and 4216 secondary school teachers in Nakuru County. Yamane formula was used to compute a sample of 374 respondents. Stratified random sampling was used to select 2 principals and 32 teachers from each of the 11 zones in the county, summing up to 22 principals and 352 teachers. Self-designed questionnaires of 5 point likert scales were used to collect data from the respondents. Data was analyzed using descriptive statistics by obtaining frequency counts and percentages, and inferentially using t-test. The findings revealed that distribution of online resources and parental engagement considerably enhanced equitable learning of vulnerable learners during the pandemic. The study recommended that the ministry of education establishes a free complimentary platform where children who could not afford internet connection or have access to radio could receive learning resources during pandemics.
Keywords: Education Systems; Vulnerable Children; Online Resources; Equitable Learning; Parental Support; Socio-emotional Support